How to Ensure Consumer Safety for Unbranded Refill Drinking Water Depots? - Anna Maria Tri Anggraini (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2023)
Drinking water is water that has been processed to meet health standard regulations. However, some water can be consumed directly without several processes if it meets health safety requirements. This research aims to ensure the safety, health, and hygiene of unbranded refilled drinking water by looking at the quality of the drinking water content following SNI (Indonesian National Standard) standards and providing recommendations to the government to protect consumers of unbranded drinking water. This research applied qualitative methods through data collection techniques Focus Group Discussion (FGD), literature studies, and field observations in Semarang and Balikpapan. This study found that some refilled drinking water depots violated applicable safety regulations. However, no legal sanctions were applied for the business actors who violated it, and no regional regulations or Mayer Regulations regulate the unbranded refilled drinking water. Therefore, efforts need to be made to foster actors, educate consumers to be smart in choosing drinking water, and the establishment of implementing regulations from the Regulation of the Minister of Health Number 492 of 2010 in supervising business actors from this research is expected to be an effort to increase consumer protection in Indonesia.